2016
DOI: 10.1515/znc-2015-0125
|View full text |Cite
|
Sign up to set email alerts
|

New flavonoid C–O–C dimers and other chemical constituents from Garcinia brevipedicellata stem heartwood

Abstract: The methanol extract of the stem heartwood of Garcinia brevipedicellata has furnished three new flavonoid C-O-C dimers, brevipedicilones A (6), B (8) and C (10), along with five previously reported flavonoid dimers, viz. amentoflavone (1), 4″'-O-methylamentoflavone (2), robustaflavone (3), 4'-O-methyl robustaflavone (4) and tetrahinokiflavone (5). The new structures, which are composed of flavanone-flavanonol or flavanonol-flavanonol sub-units, were established based on spectroscopic analysis including 1D and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The determination of the chemical profiles of FEE (fruit ethanolic extract), EEFH (hexane fraction), EEFC (chloroform fraction), EEFA (ethyl acetate fraction), EEFW (hydromethanolic fraction), EEL (ethanol leaf extract), EELH (hexane fraction), EELC (chloroform fraction), EELA (ethyl acetate fraction), and EELW (hydromethanolic fraction) were performed based on UV, MS, and MS/MS data as compared with data described in the literature [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Twenty-six compounds were tentatively identified ( Table 1 and Table 2 , Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The determination of the chemical profiles of FEE (fruit ethanolic extract), EEFH (hexane fraction), EEFC (chloroform fraction), EEFA (ethyl acetate fraction), EEFW (hydromethanolic fraction), EEL (ethanol leaf extract), EELH (hexane fraction), EELC (chloroform fraction), EELA (ethyl acetate fraction), and EELW (hydromethanolic fraction) were performed based on UV, MS, and MS/MS data as compared with data described in the literature [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Twenty-six compounds were tentatively identified ( Table 1 and Table 2 , Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 3 was isolated as a yellow powder and its molecular formula was deduced as C 15 H 14 O 4 on the basis of its (+)-HR-ESI-MS data (m/z 257.0830 [M − H] − , calcd for 257.0814). The 1 H NMR data (Table 1) of 3 showed the hydrogen signal of the ABX coupling system on the benzene ring [δ H 7.84 (1H, d, J = 8.9 Hz, H-6'), 6.34 (1H, dd, J = 8.9, 2.2 Hz, H-3′), and 6. with that of (2S, 2″S) tetrahydronokiflavone, 36 it was found that the plane structures of the two compounds were almost similar except the substitution position of the methoxy. The HMBC correlation from δ H 3.78 (3‴-OCH 3 ) to δ C 148.0 (C-3‴) suggested that the methoxy was attached to C-3‴.…”
Section: ■ Materials and Methodsmentioning
confidence: 84%
“…In comparison with literature data, isolated compound 4 was determined to be a biflavone, which was trivially named amentoflavone [16]. Secondary metabolite 4 has ever been isolated from various Garcinia species, such as G. brevipedicellata stem heartwoods, or G. livingstonei leaves, however, it was now found in G. mackeaniana [17,18] for the first time. [19], compound 5 was unambiguously determined to be methyl 3,4dihydroxybenzoate, which was trivially named methyl protocatechuate.…”
Section: The Nmr-structural Elucidationmentioning
confidence: 94%